Multilocational Households in the Global South and North: Relevance, Features and Spatial Implications - Dick, Eva; Reuschke, Darja (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Both in the Global North and South, labour-related circular migration is on the rise. However, an integrated view on multilocality in both contexts is wanting. Addressing this gap and based on primary and secondary data, this paper identifies key structural factors shaping labour-related circular migration in both South and North: economic transformation, spatial structures, transportation/communication technology, societal modernisation. It ascertains the important (albeit dissimilar) role of households in motivating multilocational living arrangements at both ends. Different spatio-temporal patterns and socio-economic characteristics of the involved households in countries of the North and South are related to dissimilar effects of the structural factors in each context.